2021
DOI: 10.2196/27052
|View full text |Cite
|
Sign up to set email alerts
|

Internet Interest in Colon Cancer Following the Death of Chadwick Boseman: Infoveillance Study

Abstract: Background Compared with White Americans, Black Americans have higher colon cancer mortality rates but lower up-to-date screening rates. Chadwick Boseman was a prominent Black American actor who died of colon cancer on August 28, 2020. As announcements of celebrity diagnoses often result in increased awareness, Boseman’s death may have resulted in greater interest in colon cancer on the internet, particularly among Black Americans. Objective This study … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 40 publications
2
12
0
1
Order By: Relevance
“…Until recently, the impact of a public figure's disclosure of illness regarding CRC was unknown. In line with our own findings, one recently published study by Naik et al [38] examined internet search interests in CRC-related topics following Chadwick Boseman's death and found increases in searches on Google and Wikipedia comparable to our own. Moreover, the study found proportionally higher increases among areas with higher proportions of Black Americans, a novel and important finding that should be used to increase CRC education among this at-risk community.…”
Section: Principal Findingssupporting
confidence: 92%
“…Until recently, the impact of a public figure's disclosure of illness regarding CRC was unknown. In line with our own findings, one recently published study by Naik et al [38] examined internet search interests in CRC-related topics following Chadwick Boseman's death and found increases in searches on Google and Wikipedia comparable to our own. Moreover, the study found proportionally higher increases among areas with higher proportions of Black Americans, a novel and important finding that should be used to increase CRC education among this at-risk community.…”
Section: Principal Findingssupporting
confidence: 92%
“…A previous study ( 68 ) of the impact of Boseman's death on web-based search interest in CRC found that relative search volume (RSV) for the topics colorectal cancer and colon cancer screening increased by 598 and 707%, respectively, and were on average 121 and 256% greater than expected during the first 3 months following Boseman's death. The race or ethnicity of those conducting these searches could not be ascertained due to the infoveillance nature of the study; however, during the 2 weeks following Boseman's death, statistically significant positive correlations, which persisted for 4 months, were seen between the RSV for colon cancer and the percentage of Black Americans per state and per metropolitan area.…”
Section: Discussionmentioning
confidence: 93%
“…The decrease in screening was likely related to the fact that elective procedures were banned as the COVID-19 pandemic worsened in the United States around March 2020. Another study similarly showed a spike in colon cancer searches around Boseman’s death in late August 2020 [ 12 ]. However, in our study, search volume for “colon cancer” and “colonoscopy” returned to their pre-pandemic levels by April 2021, which is contrary to the influence celebrities have had in the past.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, actor Chadwick Boseman died on August 28th, 2020, of colon cancer at the age of 43. While it may be too soon to see the long-term effects of Boseman’s death on colon cancer screening rates, recent research has shown that interest in colon cancer increased surrounding his death, particularly among Black Americans [ 12 ]. However, it is unclear if this interest in the disease translated into an interest in colon cancer screening and how long that effect might have lasted.…”
Section: Introductionmentioning
confidence: 99%